The Differential Practices of Post Natal Care by Socio-Cultural Background of Mothers - Acharya, Chiranjivi; Kumar, Nand Kishor (International Journal of Humanities, Education, and Social Sciences, 2025)
As WHO (1948) the postnatal period can be defined as the first 6-8 weeks after birth. Postnatal care should be a continuation of the care the woman has received through her pregnancy, labour and birth and consider the woman's individual needs and preferences. Main aimed of this article is to analyzed the differential practices of post-natal care by socio-cultural background of mothers. Descriptive and analytical research designed and deductive research approach are applied. Both primary data and secondary information are used and re-tabulated and re-described to make a rational of article. Level of education, urban residence, Terai eco-zone are most influencing factor to enhance the postnatal care of mother. Comparing with other caste/ethnic groups, Chhetri and Brahmin have more practice of postnatal care of mother.